Technologically-Treated Polyclonal Affinity-Purified Antibodies to the Tumor Necrosis Factor-α, Brain Specific S-100 Protein and Histamine in Treatment of Functional Dyspepsia: Results of the Multicenter, Randomized, Double-Blind, Placebo-Controlled Trial - Yu. O. Shulpekova; I. V. Maev; V. B. Grinevich; I. B. Khlynov; Yu. G. Shvarts; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of the study was to evaluate the efficacy and safety of Kolofort® (a complex medicine containing technologically processed forms of antibodies to S-100 protein, tumor necrosis factor-α and histamine) in the management of functional dyspepsia (FD) in outpatient clinical practice.Methods: Outpatients (N = 309) at the age of 18–45 in whom FD was diagnosed according to the Rome IV criteria were enrolled in a multicenter, double-blind, placebo-controlled, randomized clinical trial. Patients were randomized in two groups receiving Kolofort® or placebo 2 tablets tid for 8 weeks. The primary endpoint of the study was a change in the FD symptoms severity score according to the Gastrointestinal symptom score (GIS) at week 8. ITT and [PP] analysis were performed.Results: at week 8 the reduction in GIS sum score was observed in Kolofort® group and placebo group (by 7.2 ± 3.3 [7.2 ± 3.4] and 6.3 ± 4.6 [6.2 ± 4.5], respectively, p = 0.041 [0.039]). The proportion of cases with GIS score reduction by ≥4 was 88,1 % [88.6 %] and 79.1 % [79.6 %] in Kolofort® group and placebo group, respectively (p = 0.046 [p = 0.051]). None of the patients in Kolofort® group had progression of FD symptoms or required additional therapy. There were 29 adverse events (AEs) recorded in 25 patients including 16 cases in 13 (8.6 %) patients in Kolofort® group and 13 AEs in 12 (7.6 %) patients in placebo group.Conclusion: the clinical trial demonstrates the positive effect of Kolofort® in FD with a favorable safety profile.